2004
DOI: 10.1073/pnas.0407416101
|View full text |Cite
|
Sign up to set email alerts
|

RGS9-2 modulates D 2 dopamine receptor-mediated Ca 2+ channel inhibition in rat striatal cholinergic interneurons

Abstract: Regulator of G protein signaling (RGS) proteins negatively regulate receptor-mediated second messenger responses by enhancing the GTPase activity of G␣ subunits. We describe a receptor-specific role for an RGS protein at the level of an individual brain neuron. RGS9-2 and G␤5 mRNA and protein complexes were detected in striatal cholinergic and ␥-aminobutyric acidergic neurons. Dialysis of cholinergic neurons with RGS9 constructs enhanced basal Ca 2؉ channel currents and reduced D2 dopamine receptor modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 41 publications
2
81
0
Order By: Relevance
“…Furthermore, Gao is regulated by RGS9-2 in medium spiny neurons (Cabrera-Vera et al 2004), and we have found that the homologous protein EGL-10 regulates GOA-1/Gao coupled to DOP-3 in C. elegans ( Figure 1A and Chase et al 2004). Finally, D1-like receptors in the mammalian brain can couple to Gaq (Wang et al 1995), and we have shown that the C. elegans DOP-1 receptor also couples to Gaq (this work and Chase et al 2004).…”
Section: D1-like Receptors Can Act Through Gaq and D2-like Receptorsmentioning
confidence: 99%
“…Furthermore, Gao is regulated by RGS9-2 in medium spiny neurons (Cabrera-Vera et al 2004), and we have found that the homologous protein EGL-10 regulates GOA-1/Gao coupled to DOP-3 in C. elegans ( Figure 1A and Chase et al 2004). Finally, D1-like receptors in the mammalian brain can couple to Gaq (Wang et al 1995), and we have shown that the C. elegans DOP-1 receptor also couples to Gaq (this work and Chase et al 2004).…”
Section: D1-like Receptors Can Act Through Gaq and D2-like Receptorsmentioning
confidence: 99%
“…Several studies have demonstrated that the long splice isoform of RGS9 (RGS9-2) serves as a critical GAP in these neurons (9,10). In particular, RGS9-2 has been shown to regulate signaling downstream from D2 dopamine (D2R) and -opioid (MOR) receptors and has been implicated in drug addiction and movement disorders (11)(12)(13)(14)(15). However, no studies directly examined the impact of RGS9-2 on G protein dynamics activated by D2R and MOR.…”
mentioning
confidence: 99%
“…RGS2, RGS4, and RGS9-2 are known to be closely related to the dopaminergic nervous system and drug addiction (45). RGS9-2 is highly enriched in the striatum and nucleus accumbens, where it regulates the functional responses of D2-like receptors in vivo (6,28,35). Regulatory roles for RGS2 and RGS4 in the signaling of D2-like receptors have not been reported.…”
Section: Rgs9mentioning
confidence: 99%
“…It was reported that D2-like receptors are functionally regulated by RGS9-2. For example, viral expression of RGS9-2 in the nucleus accumbens or dialysis of RGS9-2 proteins into striatal cholinergic interneurons reduced the behavioral or electrophysiological response to stimulation of the D2-like receptor (6,35). On the other hand, knockout of RGS9-2 enhanced behavioral responses to the activation of D2-like receptors (28,35).…”
mentioning
confidence: 99%